Marshall or Jacobs? Answers to an unsuitable question from an interaction model - Robert Lehmann; Jan Kluge (European Regional Science Association (ERSA), 2012)
This paper investigates whether localization economies as brought forward by Marshall (1890) or urbanization economies as mentioned by Jacobs (1970) are more decisive for regional gross value added per capita. Our novel approach is to explicitly allow for interdependencies between these two theories and to take into account that the initial levels of specialization and diversification might play a role. We therefore deploy a model with interaction terms and find that these two theories are not mutually exclusive in most of our sectors. In addition, the empirical results show that the initial levels of specialization and diversification do matter as well.
Keywords: C33; O18; O40; R11; 330; localization and urbanization economies; interaction models; regional gross valued added